Enzymatic Strategies for the Preparation of Pharmaceutically Important Amino Acids through Hydrolysis of Amino Carboxylic Esters and Lactams - Forró, Enikő; Fülö p, Ferenc (Current Medicinal Chemistry, 2022)
The most relevant lipase-catalyzed strategies for the synthesis of pharmaceutically important cyclic and acyclic α-, β- and γ-amino carboxylic acid enantiomers through hydrolysis of the corresponding amino carboxylic esters and lactams, over the last decade are overviewed. A brief Introduction part deals with the importance and synthesis of enantiomeric amino acids, and formulates the objectives of the actual work. The strategies are presented in the Main Text, in chronological order, classified as kinetic, dynamic kinetic and sequential kinetic resolution. Mechanistic information of the enzymatic transformations is also available at the end of this overview. The pharmacological importance of the enantiomeric amino acids is given next to their synthesis, in the Main Text, and it is also illustrated in the Conclusions and Outlook sections.
Keywords: DKR